PENGARUH KUALITAS AUDIT DAN KOMITE AUDIT TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BEI - Shelly Julyen Sinurat; Lorina Siregar Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2023)
This study hopes to learn more about how audit quality and audit committees affect earnings management at manufacturing companies. In the year of 2020 until 2022, the research analyzed sub sector ceramic, porcelain, and glass, the manufacturing businesses trading on the Indonesia Stock Exchange. With Quantitative methods were derived through analyses of seven different companies' yearly financial reports, yielding 21 separate data sets. Using descriptive statistics, classical assumptions, multiple linear regression, hypothesis testing, and the coefficient of determination are all handled inside the SPSS software. The research found no significant relationship between audit quality or the presence of an audit committee and earnings management.